PENGARUH INOVASI PRODUK DAN KEPUASAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA ABG GUMES KOTA BIMA - Ovriyadin; Firdaus; Siti Asyitah (Hikamatzu | Journal of Multidisciplinary, 2025)
The research questions are 1) whether product innovation has a significant effect on purchasing decisions, 2) whether consumer satisfaction has a significant effect on purchasing decisions, and 3) whether product innovation and consumer satisfaction have a significant effect on purchasing decisions. This study aims to examine and determine the effect of product innovation on product purchasing decisions at ABG GUMES Bima City, and examine the effect of consumer satisfaction on purchasing decisions. Population is not known with certainty, therefore the sampling technique is done by purpusive sampling in determining the sample. The questionnaires that were successfully collected were 100 questionnaires. The results showed that there was a significant effect of product innovation on purchasing decisions. The variable of consumer satisfaction with purchasing decisions has no significant effect. Innovation must continue to be done to maintain product purchase decisions at ABG Gumes Bima City